The effects of brand image, halal label, and animosity on purchasing decision with promotion as a moderating variable: A case study of Scarlett Whitening sales at Mutiara Kosmetik Shop - Heydiana, Alma; Aliyanti, Fitri Eka (Universitas Islam Indonesia, 2024)
IntroductionThe Indonesian skincare market has experienced rapid growth, driven by increased consumer awareness and demand for affordable, high-quality products. Scarlett Whitening has emerged as a leading local brand, leveraging its brand image and halal certification. However, challenges such as limited consumer awareness of halal certification and socio-political animosity complicate purchasing decisions.ObjectivesThis study examines the influence of brand image, halal certification, and consumer animosity on purchasing decisions for Scarlett Whitening products. It also investigates the moderating role of promotional activities in these relationships.MethodA quantitative approach was adopted, using Structural Equation Modeling (SEM) to analyze data from 220 respondents at Mutiara Kosmetik in Yogyakarta, Indonesia. The study employed a structured questionnaire to measure brand image, halal certification, animosity, promotions, and purchasing decisions, ensuring validity and reliability through established scales.ResultsBrand image significantly and positively influenced purchasing decisions, highlighting its role in fostering consumer loyalty. Halal certification exhibited a negative relationship with purchasing decisions, suggesting gaps in consumer awareness. Animosity had no direct impact but was moderated by promotions, which effectively mitigated its effects. Promotions also amplified the positive influence of brand image but had limited impact on halal certification.ImplicationsThe findings underscore the importance of integrated marketing strategies that leverage brand strength, address consumer trust in ethical certifications, and mitigate socio-political challenges through targeted promotions. These insights are vital for enhancing market positioning in culturally sensitive contexts.Originality/NoveltyThis study provides a holistic framework for understanding purchasing decisions by integrating brand image, halal certification, animosity, and promotions, offering actionable recommendations for culturally and politically sensitive markets.